Optimalisasi UKS dalam Penanganan Kegawatdaruratan Dasar di Sekolah melalui Pelatihan Kegawatdaruratan Dasar bagi PMR di SMP Bayt Al-Hikmah Kota Pasuruan - Marsaid Marsaid (Jurnal Pengabdian Pada Masyarakat, 2020)
OPTIMIZING SCHOOL HEALTH (UKS) IN HANDLING BASIC EMERGENCY IN SCHOOLS THROUGH BASIC EMERGENCY TRAINING FOR RED CROSS TEEN IN BAYT AL-HIKMAH MIDDLE SCHOOL, PASURUAN CITY. Accidents and emergency conditions can occur anywhere, anytime and attack anyone. Errors or delays in initial treatment can result in the deterioration of the victim’s condition which can result in disability or other complications, not infrequently even to the point of death. At present the incidence of cardiac arrest and respiratory arrest patients is greatly increased and requires immediate assistance in rescue. Objectives of Community Service Optimization in the School Health Efforts in Handling Emergency in Schools Through Basic Emergency Training is expected that PMR members will be able to do first aid to the surrounding community who experience accidents or emergency conditions. This activity was carried out at Bayt Al-Hikmah Middle School in Pasuruan City on 29 and 31 August 2019. Community service activities consisted of theoretical training in class and skills training with a total number of participants of 50 people. The results of community service activities showed that there was a significant increase in the ability of PMR members, this was indicated by an increase in the average value of knowledge before and after the training which was 55.4 to 85.6. Participants are able to do basic first aid in cases of broken bones with splint dressing, cases of bleeding with compressive pressure, as well as handling foreign body obstruction properly. This basic first aid training activity should be carried out routinely especially for refreshing, updating and developing and fostering PMR members in schools and communities.